Pengaruh Solvabilitas dan Likuiditas Terhadap Profitabilitas dengan Nilai Tukar Sebagai Variabel Moderasi - Marcella Puspita; Cahyadi Husadha; Elia Rossa (Politeknik Kampar, 2024)
The Effect of Solvency and Liquidity on Profitability with the Exchange Rate as a Moderating Variable (Study of Banking Companies Listed on the Indonesian Stock Exchange for the 2019-2022 Period)